The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12960-015-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human resources for health programme implementation in 15 Latin American and Caribbean countries

Abstract: BackgroundThe health systems in the Americas region are characterized by fragmentation and segmentation, which constitute an important barrier to expanding coverage, achieving integrated primary health care, and reducing inefficiency and discontinuity of care.An assessment of the human resources for health (HRH) programmes that have been implemented at the country level was developed as part of the measurement of the 20 HRH regional goals for 2007–2015, adopted in 2007 by the Pan American Sanitary Conference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 9 publications
0
21
0
8
Order By: Relevance
“…[23][24][25][26] While several human resources programmes have been established and implemented at national and regional levels, it has been suggested that additional implementation take place at subnational levels. 27 Furthermore, based on the observation that both ophthalmologists and other physicians tend to make similar choices when choosing work locations, it has been suggested that a review of data regarding overall distribution of physician human resources be undertaken in order to improve the distribution of ophthalmologists. A Finnish study found no significant differences between general practitioners and eye physicians when choosing work locations.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] While several human resources programmes have been established and implemented at national and regional levels, it has been suggested that additional implementation take place at subnational levels. 27 Furthermore, based on the observation that both ophthalmologists and other physicians tend to make similar choices when choosing work locations, it has been suggested that a review of data regarding overall distribution of physician human resources be undertaken in order to improve the distribution of ophthalmologists. A Finnish study found no significant differences between general practitioners and eye physicians when choosing work locations.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher's ultimate goal should be reporting the results to the communities of interest and stake holders. According to Dal Poz et al [26], there is a growing demand for program developers in developing countries to construct and implement programs for the management and planning of human resources in health (HRH). This study demonstrates the importance of reporting evaluation results.…”
Section: Reportingmentioning
confidence: 99%
“…To begin with, the study was prompted by the identification of the crisis in the global health workforce. This crisis is characterized by a shortage of professionals, (b) supporting decision making in the formulation, implementation, or modification of health policies; and (c) expanding and maintaining a workforce able to support primary health care [26]. The evaluation reflected an effort of both academic research and the development/application of an advocacy tool.…”
Section: Reportingmentioning
confidence: 99%
See 2 more Smart Citations